Pengembangan Perangkat Pembelajaran IPA Berorientasi Model Inkuiri untuk Melatihkan Ketrampilan Proses di SD - Selly Nurina Suraya (Jurnal Pendidikan, 2010)
This research serves a thorough out-look on the effectiveness of teaching tools for Natural Science subject which are developed based on inquiry model to nurture process skill of Ekementary School students. The teaching tools developed through this research are lesson plan, BAS, students worksheet and achievement test. The research is carried out through two steps, i.e. the teaching tools development and the implementation. The research objacts are teaching tools and the subjects are the students of SDN Bareng Krajan 1 Krian. The developed teaching tools refer to Dick and Carey Model. The implementation makes use of one group pretest-posttest design. The results of analysis show that: all of the teaching tools are valid under validation test; the taching tools support learning effectiveness in nurturing process skill of Natural Science Class od Elementary School, inspite of difficulties in implementing them in research.